TEN-YEAR RETROSPECTIVE STUDY OF DIAZEPAM CONSUMPTION IN INDONESIA - Priyatni, Nunung; Hasanbasri, Mubasysyir; M, Mustofa; Suryawati, Sri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to evaluate annual consumption during 2004-2013 of diazepam, an essential medicine which is controlled under the 1971 Convention on Psychotropic Substances in Indonesia and to investigate factors influencing its use in health facilities. Methods: This was a case study with quantitative and qualitative approaches. Annual consumption was calculated from the quantity of exports and imports. The use of diazepam was calculated from consumption deducted by 20% buffer stock. The consumption and use of diazepam were presented in kilogram and also in defined daily doses for statistical purposes (S-DDD). In-depth interviews were conducted to investigate factors that influence the use of diazepam. Triangulation was conducted to confirm the qualitative and quantitative findings. Results: The annual average consumption in 2004-2006 was 530 kg. Furthermore, it decreased 38% during 2011-2013 to 329 kg. Calculated use of diazepam also decreased. The average consumption for the 10-year period of diazepam was 470 kg, and the calculated use was 376 kg (0.45 S-DDD). Considering the approximate need of diazepam to treat various health problems, its use should ideally be around 1-2 S-DDD. Therefore, the calculated use of diazepam was considered too low as confirmed by frequent stockouts. The interviews revealed that among the factors influencing its use was its limited production. There was an increased use of alprazolam, but it was unlikely to compensate for the diazepam stockouts. Conclusion: Consumption and use of diazepam for medical purposes in Indonesian decreased over 10 years, and stockouts are often reported. The government should improve its availability and correct impediments for adequate production and supply of diazepam.